Antigens from Taenia crassiceps cysticerci used in complement fixation, enzyme-linked immunosorbent assay, and western blot (immunoblot) for diagnosis of neurocysticercosis. - Garcia, E (1995)
Antigens from Taenia solium cysticerci for the immunodiagnosis of cysticercosis are scarce and difficult to obtain. We studied the reliability of antigens from Taenia crassiceps cysticerci as a substitute for those from T. solium in three diagnostic tests: complement fixation, enzyme-linked immunosorbent assay, and Western blot (immunoblot). Precision rates of the three tests of 93, 99, and 96%, respectively, were found. Cysticerci from T. crassiceps can be easily obtained in large quantities and can be effectively used for the diagnosis of human neurocysticercosis.